Cloning, nucleotide sequence, and expression of the Rhodobacter sphaeroides Y thioredoxin gene. - Pille, S (1990)
Synthetic oligodeoxynucleotide probes based on the known amino acid sequence of Rhodobacter sphaeroides Y thioredoxin were used to identify, clone, and sequence the structural gene. The amino acid sequence derived from the DNA sequence of the R. sphaeroides gene was identical to the known amino acid sequence of R. sphaeroides thioredoxin. An NcoI site was created by directed mutagenesis at the beginning of the thioredoxin gene, inducing in the encoded protein the replacement of serine in position 2 by alanine. The 421-base-pair NcoI-PstI restriction fragment obtained was ligated in the pKK233-2 expression vector and the resulting hybrid plasmid was used to transform Escherichia coli strains lacking functional thioredoxin. Transformants that complemented mutations in the trxA gene were identified by increased colony size on rich medium, growth on minimal medium with methionine sulfoxide, and ability to support M13 growth and T7 replication; this latter phenotype implies correct interaction between R. sphaeroides thioredoxin and the product of T7 gene 5. The presence of R. sphaeroides thioredoxin was further confirmed by enzyme assay.